Intake and digestibility of untreated and urea treated rice straw base diet fed to sheep - Yulistiani, D; Gallagher, J.R; Barneveld, R.J. Van (Indonesian Journal of Animal and Veterinary Sciences, 2003)
Rice straw as one of agricultural by-products has low quality due to low content of essensial nutrients like protein, energy, minerals and vitamin as well as poor palatability and digestibility. Therefore, the quality of rice straw needs to be improved in order to increase its utilization by gastrointestinal tract of ruminants. The purpose of this study is to compare untreated and urea treated rice straw as basal diets for sheep. Twelve mature Merino wethers (average body weight 53.62 + 3.44 kg) were separated into 4 groups based on their live weight with each groups assigned three diets, that are: diet 1 untreated rice straw with high forage legume content, diet 2 urea ensiled rice straw and diet 3 rice straw sprayed with urea solution at feeding time. Diets were allocated based on a randomized complete block design. Urea ensiled rice straw was prepared by spraying chopped straw with urea solution to yield straw containing 4% urea and 40% moisture, then kept in air tight polythylene bags for 6 weeks. The untreated, ensiled and urea supplemented rice straw were mixed with other feed ingredients to provide isoenergetic and isonitrogenous diets. Diets were formulated to meet maintenance requirement according to NRC. Sheep were adapted to experimental diets for 15 days, and after adaptation period, a metabolism trial was conducted. Results reveal that dry matter intake permetabolic body weight (DMI/W0.75), DE (digestible energi) intake and apparent digestibility of NDF (neutral detergent fibre) were not significantly different between diet 1 and diet 2. Apparent digestibility of DM (dry matter), OM (organic matter), and ADF (acid detergent fibre), as well as N retention were not significantly different between three diets. Positive result in N retention was only observed in diet 2, while others were negative. It may be concluded from this study that untreated rice straw basal diet supplemented with forage legume offer an alternative method other than urea ensiled for improving the nutritional value of rice straw as a ruminant feed on small farmer. Â  Key words: Rice straw, urea treated, digestibility, and sheep